R-ver Mat: uma proposta para recuperação paralela de conteúdos de matemática no ensino médio - Santos, Eliana Calixto (2020)
This thesis presents a proposal for parallel online recovery, developed in the Blended Learning modality and its Flex model, for the mathematics and related disciplines of the technical vocational courses of medium level in the Jacareí campus of the Federal Institute of São Paulo - IFSP.The presented proposal is justified because the parallel recovery in the disciplines that demand previous knowledge of mathematics needs to be offered as soon as the student enters the institution or before the discipline starts its academic year. The proposal presented in this thesis, called R-ver Mat, was developed and made available in the Moodle of the IFSP, considering the integration of the mathematics contents already studied in the elementary and high school, with those of the subjects of the technical courses. The theoretical basis of this research was based on the learning theory of Ausubel (1968) and aspects of Valente's Learning Cycle and Spiral theory, as supports for the construction of the proposal and analysis of the student's learning process during his participation in the available modules. The research methodology considered the assumptions of Brown's Design Experiments (1992), which enabled the improvement of the three versions presented in this thesis. Most of the research subjects performed better compared to those of the diagnostic evaluation. The results also point to the acceptance of the R-ver Mat program, both by the institution and by some teachers of the courses involved, indicating the continuity of the proposal